Dual Isotope Measurements Reveal Zoning of Nitrate Processing in the Summer Changjiang (Yangtze) River Plume. Issue 24 (18th December 2017) - Yan, Xiuli; Xu, Min Nina; Wan, Xianhui Sean; Yang, Jin‐Yu Terence; Trull, Thomas W.; Dai, Minhan; Kao, Shuh‐Ji
Abstract: Riverine nitrogen input into the coastal zone has increased remarkably in recent decades. Yet its transformation and recycling within hydrodynamically active regions remains unclear. Using observations of nitrate concentration and dual isotopic composition across the Changjiang River plume within a three end‐member mixing model, we found deviations between the observed and expected values for mixing alone, revealing the nonconservative behavior of nitrate. Using cross correlations between concentrations and dual isotope deviations, we identified three nitrogen transformation zones, which correspond to separate portions of the plume. Nitrification and sedimentary denitrification occurred near the river mouth, nitrification prevailed further offshore under the plume, and finally, phytoplankton assimilation occurred in the outer surface plume (>100 km offshore), where it was fueled by nitrate that had already been strongly modified by microbial processes. Information was assembled into a conceptual model offering an overview of nitrogen transformations in a large river plume. Key Points: Three zones with different nitrogen processes were identified using isotopic composition, and these correspond to different physical regimes Primary producers in coastal waters utilized nitrate that has already been microbially altered and recycled Caution is required to derive biological isotope effects in a plume using the initial nitrate composition of the freshwater end‐member